FATTY ACID PROFILE AND SENSORY PROPERTIES OF ROE DEER MEAT AFTER MODIFIED ATMOSPHERE STORAGE - DASZKIEWICZ, T.; KONDRATOWICZ, J. (Italian Journal of Food Science, 2020)
The aim of this study was to determine the effect of cold storage (2°C, 7 and 21 days) under vacuum and modified atmosphere (MA) conditions on the fatty acid (FA) profile and sensory properties of the Longissimus thoracis et lumborum from male roe deer. The total content of polyunsaturated FA tended to decrease during storage. Storage conditions had a limited (P>0.05) influence on the FA composition. Vacuum- and MA-packaged meat was characterized by high sensory quality during storage. However, samples packaged in MA composed of 40% CO2+60% N2 had a tendency to higher average scores for taste desirability after the third week of storage.